Los quironómidos (Diptera) y su empleo como bioindicadores - Paggi, Analía Constancia (2004)
The use of chironomids as indicator organisms of the water quality and in the classification of the different aquatic environments demonstrated mainly along the history of Limnology in the Northern Hemisphere was pointed out. The temporal- spatial distribution of Chironomidae in the Limay River (Patagonia) and in the Grande River (San Luis) as part of the studies carried out until present to characterize different running waters were commented. The growing interest for the studies of environmental impact in our country, using the benthic macroinvertebrates, and among them the chironomids, was analyzed through out a monitoring study carried out in the Matanza - Riachuelo basin by the application of the IMRP biotic index with the purpose to evaluate the biological status of these area. The analysis of the pupal exuviae from the drift of flowing waters besides their taxonomical value in biodiversity progress and their use in pollution assessments, starting from the knowledge of the tolerant and non tolerant species to the contamination, was suggested for the region.